Correlation of Lipid Profile and Apolipoprotein B/A-I Ratio with Insulin Resistance in Non-Diabetes Mellitus Subjects - Andi Heriadi Palloge; Liong Boy Kurniawan; Yuyun Widyaningsih; Husaini Umar; Nurahmi Nurahmi; Andi Alfian Zainuddin (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2023)
Obesity is defined as an increase in total body mass due to excess fat, as measured by the body mass index. Obesity affects metabolism through factors such as insulin resistance, which triggers the development of chronic diseases. Lipid and ApoB/ApoA-I ratios can be considered additional assessments, especially in patients at high risk of cardiovascular diseases such as diabetes. This study aims to determine the relationship between lipid and ApoB/ApoA-I ratios with Homa-IR in in non-diabetes mellitus adult subjects. The method used in this study was a cross-sectional study involving a total of 80 non-diabetic adult subjects, consisting of 38 male and 42 female subjects. The results showed that there were significant differences between the ratios of CHOL/HDL, TG/HDL, ApoB/ApoA-I, and HOMA-IR in non-obese and obese non-DM adult subjects (4.64 ± 2.18 vs 5.23 ± 1.87, p = 0.045; 2.38 ± 1.20 vs. 3.18±1.77, p=0.013;0.58±0.17 vs. 0.66±0.17, p=0.035 and 1.47±0.80 vs. 3.34±4.37, p = 0.000), and there was no significant difference between LDL/HDL (p = 0.117). The correlation test results between the ratios of CHOL/HDL to HOMA-IR, LDL/HDL to HOMA-IR, TG/HDL to HOMA-IR, and ApoB/ApoA-I to HOMA-IR in non-DM adult subjects (p=0.05, r=0.308; p=0.037, r=0.233; p=0.000, r=0.402; p=0.19, r=0.261). This study concluded that there was a significant correlation between lipid and ApoB/ApoA-I ratios with Homa-IR in non-diabetes mellitus adult subjects.